2012
DOI: 10.1016/j.cub.2012.03.013
|View full text |Cite
|
Sign up to set email alerts
|

A Causal Link between Visual Spatial Attention and Reading Acquisition

Abstract: Reading is a unique, cognitive human skill crucial to life in modern societies, but, for about 10% of the children, learning to read is extremely difficult. They are affected by a neurodevelopmental disorder called dyslexia. Although impaired auditory and speech sound processing is widely assumed to characterize dyslexic individuals, emerging evidence suggests that dyslexia could arise from a more basic cross-modal letter-to-speech sound integration deficit. Letters have to be precisely selected from irrelevan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
386
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 449 publications
(422 citation statements)
references
References 52 publications
28
386
0
8
Order By: Relevance
“…Alternative theories have suggested that RD is rooted in abnormalities in visual processing (Demb et al 1998) and visualspatial attention (Facoetti et al 2000;Franceschini et al 2012). In the present study, right hemisphere connectivity between AG and pericalcarine cortex positively correlated with phonemic decoding.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Alternative theories have suggested that RD is rooted in abnormalities in visual processing (Demb et al 1998) and visualspatial attention (Facoetti et al 2000;Franceschini et al 2012). In the present study, right hemisphere connectivity between AG and pericalcarine cortex positively correlated with phonemic decoding.…”
Section: Discussionsupporting
confidence: 60%
“…Many studies have highlighted abnormalities in visuospatial attention in RD (Facoetti and Molteni 2001;Hari et al 2001;Facoetti et al 2003Facoetti et al , 2006Sireteanu et al 2005;Liddle et al 2009;Facoetti, Corradi et al 2010;Facoetti, Trussardi et al 2010). Converging evidence also suggests that difficulties in visuospatial attention are an important predictor of reading abilities (Valdois et al 2004;Shaywitz and Shaywitz 2008;Franceschini et al 2012Franceschini et al , 2013. Reading remediation (Franceschini et al 2013) may rely largely on alterations in visual or auditory attentional functions of the dorsal attention network (Ronconi et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is thought to be subsumed by the anterior cingulate cortex (Dosenbach et al, 2006(Dosenbach et al, , 2007. Deficits in attentional processing seem to be linked to some important neurodevelopmental disorders such as dyslexia and autism spectrum disorder (Franceschini, Gori, Ruffino, Pedrolli, & Facoetti, 2012;Franceschini, Gori, Ruffino, Viola, Molteni, & Facoetti, 2013;Ronconi, Gori, Giora, Ruffino, Molteni, & Facoetti. 2013;Gori, Cecchini, Bigoni, Molteni, & Facoetti, 2015, for review see: Vidyasagar & Pammer, 2010).…”
mentioning
confidence: 99%
“…Also proposed is that a causal link exists between reading deficits and phonologic problems involving the capture of auditory and visual automatic attention. There is evidence pointing to the presence of a cross-modal letter-to-speech sound integration deficit [7]. Facoetti, Lorusso, Cattaneo, Galli and Molteni suggest that focused spatial attention (FSA), a crucial factor affecting multimodal perceptual processing efficiency, enhances neural representation of the attended stimuli by faster reaction times, improved sensitivity and reduced flanker effect [8].…”
Section: Manipulation Of Attention In Children With Readingmentioning
confidence: 99%